Phenotyping the Immune Response to Trauma: A Multiparametric Systems Immunology Approach*. Issue 9 (September 2017) - Seshadri, Anupamaa; Brat, Gabriel A.; Yorkgitis, Brian K.; Keegan, Joshua; Dolan, James; Salim, Ali; Askari, Reza; Lederer, James A.
Abstract : Objective: Trauma induces a complex immune response that requires a systems biology research approach. Here, we used a novel technology, mass cytometry by time-of-flight, to comprehensively characterize the multicellular response to trauma. Design: Peripheral blood mononuclear cells samples were stained with a 38-marker immunophenotyping cytometry by time-of-flight panel. Separately, matched peripheral blood mononuclear cells were stimulated in vitro with heat-killed Streptococcus pneumoniae or CD3/CD28 antibodies and stained with a 38-marker cytokine panel. Monocytes were studied for phagocytosis and oxidative burst. Setting: Single-institution level 1 trauma center. Patients or Subjects: Trauma patients with injury severity scores greater than 20 ( n = 10) at days 1, 3, and 5 after injury, and age- and gender-matched controls. Interventions: None. Measurements and Main Results: Trauma-induced expansion of Th17-type CD4 + T cells was seen with increased expression of interleukin-17 and interleukin-22 by day 5 after injury. Natural killer cells showed reduced T-bet expression at day 1 with an associated decrease in tumor necrosis factor-β, interferon-γ, and monocyte chemoattractant protein-1. Monocytes showed robust expansion following trauma but displayed decreased stimulated proinflammatory cytokine production and significantly reduced human leukocyte antigen - antigen D related expression. Further analysis of trauma-induced monocytes indicated that phagocytosis was no different from controls. However, monocyte oxidative burst after stimulation increased significantly after injury. Conclusions: Using cytometry by time-of-flight, we were able to identify several major time-dependent phenotypic changes in blood immune cell subsets that occur following trauma, including induction of Th17-type CD4 + T cells, reduced T-bet expression by natural killer cells, and expansion of blood monocytes with less proinflammatory cytokine response to bacterial stimulation and less human leukocyte antigen - antigen D related. We hypothesized that monocyte function might be suppressed after injury. However, monocyte phagocytosis was normal and oxidative burst was augmented, suggesting that their innate antimicrobial functions were preserved. Future studies will better characterize the cell subsets identified as being significantly altered by trauma using cytometry by time-of-flight, RNAseq technology, and functional studies. Abstract : Supplemental Digital Content is available in the text.